Perjanjian Indonesia Arab Saudi Terhadap Penempatan dan Perlindungan Pekerja Dalam Negeri - Azqa Nadirah Piliang; Riana Esterdina; Tamaulina Br Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
Establishing relations and cooperation between countries to achieve the goal of meeting the needs of each country, carrying out bilateral relations through the Agreement on the Placement and Protection of Domestic Workers between Indonesia and Saudi Arabia and establishing cooperative relations and protection of Indonesian migrant workers. The essence of the problem that will be discussed in this research is the protection that Indonesian workers in Saudi Arabia received after the Placement and Protection Agreement occurred. In carrying out this research, we used a normative juridical method, namely data collection techniques from journals, books and the internet, of course as a reference for the relationship between Indonesia and Saudi Arabia. The results of this research showed that the governments of Indonesia and Saudi Arabia agreed to form an MoU or Memorandum of Understanding with Saudi Arabia regarding the placement and protection of Indonesian workers in Saudi Arabia and on February 19 2014, the Indonesian government signed a Memorandum of Understanding with Saudi Arabia. regarding agreement regarding the placement and protection of Indonesian workers in the Domestic sector. The impact that occurred on the signing of the Moment of Understanding was to be able to maintain the protection of the rights and welfare of Indonesian Workers residing in Saudi Arabia.